Proptosis - A Clinical Profile - Dr.V.Murali Krishna M.S, ,Dr.P.Madhuri, Dr.A.P.R.Naidu M.S, Dr.V.Satya Srinivas M.S (International Journal of Scientific Research and Management (IJSRM), 2015)
To study the cases of proptosis attending the Government Hospital, Kakinada and to analyse the various aetiological factors of proptosis and to correlate various investigative modalities with the clinical diagnosis. In cases attending the Government hospital which gives a bird’s eye view of East, west Godavari and parts of Visakhapatnam districts of Andhra Pradesh, an attempt is also made to confirm the diagnosis with the methods available in the institution and also by histopathological examination in some cases.A cure and comfort is given to the extent possible in this institution